2005
DOI: 10.1529/biophysj.104.057257
|View full text |Cite
|
Sign up to set email alerts
|

Supported Membrane Composition Analysis by Secondary Ion Mass Spectrometry with High Lateral Resolution

Abstract: The lateral organization of lipid components within membranes is usually investigated with fluorescence microscopy, which, though highly sensitive, introduces bulky fluorophores that might alter the behavior of the components they label. Secondary ion mass spectroscopy performed with a NanoSIMS 50 instrument also provides high lateral resolution and sensitivity, and many species can be observed in parallel without the use of bulky labels. A tightly focused beam (approximately 100 nm) of Cs ions is scanned acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…We have advocated the use of multiple-isotope mass spectrometry 35 (MIMS) using a NanoSIMS (Cameca Instruments) as an imaging tool for interrogating membrane composition. 3639 This technique requires isotopic labeling or atom exchange (e.g. with F) of membrane components but can generate molecule-specific images with high spatial resolution, high sensitivity, and high mass resolving power, and calibration samples can be used to obtain quantitative estimates of the composition of each component.…”
Section: Introductionmentioning
confidence: 99%
“…We have advocated the use of multiple-isotope mass spectrometry 35 (MIMS) using a NanoSIMS (Cameca Instruments) as an imaging tool for interrogating membrane composition. 3639 This technique requires isotopic labeling or atom exchange (e.g. with F) of membrane components but can generate molecule-specific images with high spatial resolution, high sensitivity, and high mass resolving power, and calibration samples can be used to obtain quantitative estimates of the composition of each component.…”
Section: Introductionmentioning
confidence: 99%
“…21, 23, 2830 Because this instrument detects monoatomic and diatomic secondary ions, each species of interest must contain a distinct stable isotope so that the secondary ions generated during NanoSIMS analysis can be linked to the parent molecule. 21 The distinct stable isotopes that encode for component identity can be selectively incorporated into cholesterol and specific lipid species with established metabolic labeling techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorine is an attractive candidate elemental label due to its low abundance in biological materials and high secondary ion yields. 21, 28 Methods to conjugate small fluorine-containing molecules to antibodies have been developed for positron-emission tomography applications. 35, 36 However, we experimentally found that functionalizing antibodies with the high numbers of fluorinated molecules that enable sensitive detection with NanoSIMS compromised antibody binding.…”
Section: Introductionmentioning
confidence: 99%
“…26-29 Briefly, counts for each ion species are summed and then the ratios 19 F − / 12 C 2 − , 13 C 12 C − / 12 C 2 − , 2 H − / 12 C 2 − , and 12 C 15 N − / 12 C 14 N − are calculated. Calibration curves obtained from standard samples are then employed (see Figure S3 and Table S1) to determine the percent molar content for each component of interest.…”
Section: Resultsmentioning
confidence: 99%